Consumer palatability scores and volatile beef flavor compounds of five USDA quality grades and four muscles - Legako, J. F.; Brooks, J. C.; O'Quinn, Travis G.; Hagan, T. D. J.; Polkinghorne, R.; Farmer, L. J.; Miller, M. F. (My University, 2015)
Proximate data, consumer palatability scores and volatile compounds were investigated for four beef muscles (Longissimus lumborum, Psoas major, Semimembranosus and Gluteus medius) and five USDA quality grades (Prime, Upper 2/3 Choice, Low Choice, Select, and Standard). Quality grade did not directly affect consumer scores or volatiles but interactions (P < 0.05) between muscle and grade were determined. Consumer scores and volatiles differed (P < 0.05) between muscles. Consumers scored Psoas major highest for tenderness, juiciness, flavor liking and overall liking, followed by Longissimus lumborum, Gluteus medius, and Semimembranosus (P < 0.05). Principal component analysis revealed clustering of compound classes, formed by related mechanisms. Volatile n-aldehydes were inversely related to percent fat. Increases in lipid oxidation compounds were associated with Gluteus medius and Semimembranosus, while greater quantities of sulfur-containing compounds were associated with Psoas major. Relationships between palatability scores and volatile compound classes suggest that differences in the pattern of volatile compounds may play a valuable role in explaining consumer liking.
Keywords: Beef; Flavor; GC-MS; HS-SPME; Muscle; USDA Quality Grade